2015
DOI: 10.1016/j.foodpol.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Identifying viewpoints on innovation in low-input and organic dairy supply chains: A Q-methodological study

Abstract: In a rapidly changing ecological, economic and political environment, environmentally sustainable and energy-efficient farming systems are required (SCAR, 2008). The development and adoption of innovation are critical to improve the competitiveness of organic and low-input dairy systems. Understanding the viewpoints of dairy supply-chain members on acceptable innovation is important to be able to improve organic and low-input dairy supply chains. This study uses Stephenson?s Q methodology to investigate the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
17
0
2
Order By: Relevance
“…A further outcome was a list of innovative sustainable production strategies that represented a sort of "wish-list" of potential innovations in management practices and adapted breeds along the whole organic and low-input conventional dairy farming supply chain, and especially among dairy farmers [9,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further outcome was a list of innovative sustainable production strategies that represented a sort of "wish-list" of potential innovations in management practices and adapted breeds along the whole organic and low-input conventional dairy farming supply chain, and especially among dairy farmers [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Following the managerial literature, sustainable production strategies may be defined as broad long-term action plans that provide a road map for achieving the farmer's goals in terms of sustainable farming. The three strategies have been selected after preliminary qualitative research reported elsewhere [9,10] as potential innovative solutions to increase the competitiveness and sustainability of organic and low-input conventional dairy supply chains. The objective of our study was to assess the acceptance of these strategies and its determinants in order to inform relevant extension and other policies.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous qualitative results indicate that 'Prolonged maternal feeding' is likely be the most appealing strategy to consumers [10], but cannot be applied with success without an increased level of information from farm to fork. The level of information about the likely impact of this strategy among dairy farmers is very low.…”
Section: Discussionmentioning
confidence: 98%
“…Q-methodology is gaining popularity in the sustainability domain and agricultural research. Examples of applications in these domains include research on sustainability and environmental discourses (Barry & Proops, 1999;Curry, Barry, & McClenaghan, 2013); organic farming (Mandolesi et al, 2015); and rural innovation and research (Hermans et al, 2012;Previte, Pini, & Haslam-McKenzie, 2007). Q-Methodology allows obtaining individual perspectives on sustainability and environmental issues and analyzing differences and similarities in perspectives on these matters.…”
Section: Method: Q-methodologymentioning
confidence: 99%
“…Q-methodology consists of six stages: generating the concourse, formulating a Q-set, selecting respondents, Q-sorting, analyzing Q-factors, and perspective of the results (Barry & Proops, 1999;Cuppen, 2010;Hermans et al, 2012;Mandolesi et al, 2015). The first stage (generating the concourse) refers to the collection of statements covering all possible prevailing views on a certain topic (Hermans et.al., 2011;Mandolesi et.al., 2015), sustainable agriculture in the case of this chapter.…”
Section: Procedures and Samplingmentioning
confidence: 99%